Pertanggungjawaban Pidana Penebangan Liar Wilayah XXX (Nomor Putusan : Nomor XXX/XXXX/XXXX/XXXX) - Siregar, Nico Demus; Petrus Irwan Panjaitan; Edward ML Panjaitan (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Illegal logging in the Pasangkayu region of West Sulawesi has become a serious threat to forest sustainability. Forests, vital for ecosystems and human livelihood, are often exploited irresponsibly for personal gain, such as agriculture or timber sales. Based on Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction, particularly Article 82, individuals involved in illegal logging can be held criminally liable if they meet the elements of a criminal act (actus reus) and criminal intent (mens rea). This study uses a normative juridical approach with descriptive analysis to examine legal accountability. In the Pasangkayu case, the perpetrators were proven guilty of illegal logging, with no grounds for justification or excuse. The court confiscated key evidence, including 280 pieces of timber, a timber transport vehicle, a saw, and a Toyota Land Cruiser. Criminal liability is imposed when the unlawful act is committed intentionally, and the perpetrator is aware that their actions violate the law. Therefore, legal enforcement must ensure that all elements of the offense are fulfilled to impose appropriate sanctions and deter future violations.